ChemInform Abstract: Direct Amidation of Aldehydes with Primary Amines under Mild Conditions Catalyzed by Diolefin‐Amine—RhI Complexes. Issue 37 (22nd August 2013) - Rodriguez‐Lugo, Rafael E.; Trincado, Monica; Gruetzmacher, Hansjoerg
Abstract The reaction tolerates aliphatic, aromatic, and heteroaromatic aldehydes and amines and proceeds with ammonia as well.